Maritime Constitution - Oksep Adhayanto (Jurnal Selat, 2014)
State of Indonesia is a country of Islands (Archipelago State), which consists of small islands as well as large and sea area larger than the land area. Geographical conditions is certainly going to require various forms of policies and legislation that have maritime pattern. Experience State of Indonesia ± 69 years gives a description of that in terms of public policy and legislation are born tend to be oriented on the mainland (continental oriented) from the ocean (archipelago oriented). Maritime should be viewed as an object that contains covers many areas of life in which between one and interrelated with other fields. In the "maritime" there are many areas that can be developed such as the legal, cultural, social, engineering and marine fisheries and of course itself. Already after the 1945 amendment ought be the starting point in the unification of maritime perception saw it as having the benefit of the various aspects. Support the legislation in drafting the legal framework of maritime Indonesia's development should be one of the priorities in the development of law in Indonesia is better. Change of paradigm and mindset of the management of the State of aspects of the legislation that is based on a maritime course must be started from a higher rule, the Constitution or the Constitution of Republic of Indonesia in 1945. Keywords : Maritime, Constitution, Maritime Constitution